Poly(crotonic acid-co-2-acrylamido-2-methyl-1-propanesulfonic acid)-metal complexes with copper(II), cobalt(II), and mckel(11): Synthesis, characterization and antimicrobial activity - Soykan, Cengiz; Coskun, Ramazan; Kirbag, Sevda (Pergamon-Elsevier Science Ltd, 2007)
Poly(crotonic acid-co-2-acrylamido-2-methyl-1-propanesulfonic acid) [P(CrA-co-AMPS)] (44.22:55.78) copolymer was prepared in N,N-dimethylformamide solution using the benzoyl peroxide (Bz(2)O(2)) as initiator. Cu(II), Ni(II) and Co(II) chelates of the copolymer were prepared and the formation constants of each complex were determined by the mole-ratio method using UV-vis spectroscopy. UV-vis studies showed that the complex formation tendency increased in the followed order: Cu(II) > Ni(II) > Co(II). The copolymer and its metal chelates were characterized by FTIR, TGA, X-ray diffraction and SEM analysis. Also, in vitro antimicrobial activity of the polymers were tested on various bacteria, and yeast. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: poly(crotonic acid-co-2-acrylamido-2-metliyl-1-propanesulfonic acid); thermogravimetric analysis; polymer metal chelates; UV-vis spectroscopy; SEM analysis